Reevaluating diagnostic categories and associated malignancy risks in thyroid core needle biopsy - Chan Kwon Jung (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
As the application of core needle biopsy (CNB) in evaluating thyroid nodules rises in clinical practice, the 2023 Korean Thyroid Association Management Guidelines for Patients with Thyroid Nodules have officially recognized its value for the first time. CNB procures tissue samples preserving both histologic structure and cytologic detail, thereby supplying substantial material for an accurate diagnosis and reducing the necessity for repeated biopsies or subsequent surgical interventions. The current review introduces the risk of malignancy within distinct diagnostic categories, emphasizing the implications of noninvasive follicular thyroid neoplasm with papillary-like nuclear features on these malignancy risks. Prior research has indicated diagnostic challenges associated with follicular-patterned lesions, resulting in notable variation within indeterminate diagnostic categories. The utilization of mutation-specific immunostaining in CNB enhances the accuracy of lesion classification. This review underlines the essential role of a multidisciplinary approach in diagnosing follicular-patterned lesions and the potential of mutation-specific immunostaining to strengthen diagnostic consensus and inform patient management decisions.